Anti-Apolipoprotein A-1 IgG Levels Predict Coronary Artery Calcification in Obese but Otherwise Healthy Individuals. (7th November 2012) - Quercioli, Alessandra; Montecucco, Fabrizio; Galan, Katia; Ratib, Osman; Roux-Lombard, Pascale; Pagano, Sabrina; Mach, François; Schindler, Thomas H.; Vuilleumier, Nicolas
Abstract : We aimed at determining whether anti-apolipoprotein (apo) A-1 IgG levels are independent predictors of coronary artery calcification (CAC) and coronary endothelial dysfunction in obese and nonobese subjects without cardiovascular disease. 48 nonobese and 43 obese subjects were included. CAC score was measured by thorax scanner and defined by an Agatston score > 0. Coronary endothelial dysfunction was determined by measuring myocardial blood flow responses to cold pressor test (CPT) on PET/CT. Serum anti-apoA-1 IgG levels were measured by ELISA. Prevalence of coronary calcification was similar between the two study groups, but the prevalence of coronary endothelial dysfunction was higher in obese subjects. Anti-apoA-1 IgG levels and positivity rate were higher in obese than in nonobese individuals. CAC score was higher in anti-apoA-1 IgG positive subjects. ROC analyses indicated that anti-apoA-1 IgG levels were significant predictors of CAC > 0, but not of coronary endothelial dysfunction with a negative predictive value of 94%. Anti-apoA-1 IgG positivity was associated with a 17-fold independent increased risk of CAC > 0. In conclusion, those preliminary results indicate that anti-apoA-1 IgG autoantibodies are raised in obese subjects and independently predict the presence of coronary calcification in this population but not the presence of coronary endothelial dysfunction.